Penerapan Model Pembelajaran Berbasis Teks pada Mata Pelajaran Bahasa Inggris di SMPN 2 Kumai - Suratinem Suratinem (Anterior Jurnal, 2022)
This study aims to determine student learning outcomes in English subjects by applying text-based learning, increasing activity, and student learning outcomes. The results showed that the learning process using the Text-Based Learning model was BKOF (Building Knowledge of Field), MOT (Modelling of Text), and JCOT (Join Construction of Text). The implementation of the research from cycle 1 to cycle 2 has improved. This study shows that student learning outcomes have increased after the action. The percentage of students who have not completed continues to decline from cycle 1 to cycle 2 (from 26.47% to 8.82%). The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 73.53% to 91.18%). The indicator of the success of this CAR is that this CAR is said to be successful if the percentage of students whose learning outcomes are assessed as complete reaches a minimum of 85%. The table shows that the percentage of students whose grades have been completed has reached 91.18%, so this CAR has been successful.